复述作为提高共同希望语言学院2021届的学生汉语能力分析 - Christy Belinda; Nia Therenica (Sinolingua: Journal of Chinese Studies, 2024)
The research title of this article is "Analysis of Retelling as an Improvement of Chinese Proficiency for Students of the Class of 2021 at Common Hope Language Institute." Speaking is the most important factor in learning Chi-nese. Nowadays, many people have begun to communicate in Chinese, and Chinese has become the second international language. Nowadays, many companies are recruiting employees with Chinese language skills. There-fore, learning Chinese can increase our own value. The purpose of the study is whether retelling can be a learning and practice medium for improving Chinese speaking ability. The research subjects of this article are students from the Class of 2021 at the Common Hope Language Institute. The author used simulation methods to collect data and descriptive qualitative methods to analyze the collected data. According to the results of the study, the re-telling learning method is a learning and practice medium that can improve Chinese speaking ability. This retelling method needs to be used frequently to be effective. This article also loads the factors that affect a person's Chinese speaking ability and the most common mistakes that a person makes when speaking Chinese.